3Is Social Media the 4th ‘S’ – The Extended Perspectives of ‘Sun, Sea and Sand’ (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The trio of ‘sun, sea and sand’ has been regarded as the conventional combination of attractions that pulled the tourists to a destination and made them completely satisfied. People wishing for relaxation and enjoyment intentionally visited places that were isolated from the outside world and nobody could disturb them during their vacation. Nowadays, this situation took a big turn, and most of the tourists cannot imagine that they spend a few days without an internet connection or their smartphones.  In the era of smart devices, people are always connected to others and feel compelled to share their experiences even during their holidays. Social media not only permeates our lives but also has a powerful effect on our decisions and activities regarding our travels, as well. Travelling without posting on social media platforms is almost unbelievable nowadays. The aim of this paper is to reveal and analyse the situation based on a survey conducted with Hungarians.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.